Comparative risk of acute myocardial infarction for anti-osteoporosis drugs in primary care: a meta-analysis of propensity-matched cohort findings from the UK Clinical Practice Research Database and the Catalan SIDIAP Database - Khalid, S; Calderon-Larranaga, S; Sami, A; Hawley, S; Judge, A; Arden, N; Van Staa, TP; Cooper, C; Abrahamsen, B; Javaid, MK; Prieto-Alhambra, D (Springer, 2022)
Summary The aim of this study was to evaluate the risk of acute myocardial infarction in patients taking osteoporosis medication. Patients were taken from the SIDIAP or CPRD database and were matched using propensity scores. Patients with diabetes and chronic kidney disease taking SERMs were at an increased risk. The results favour the cardiovascular safety of alendronate as a first-line choice for osteoporosis treatment.